Production of H2-rich syngas from gasification of unsorted food waste in supercritical water. (1st February 2020) - Su, Hongcai; Kanchanatip, Ekkachai; Wang, Defeng; Zheng, Rendong; Huang, Zhicheng; Chen, Yang; Mubeen, Ishrat; Yan, Mi
Highlights: The gasification of unsorted food waste was conducted in supercritical water. Effect of main operating condition on H2 -rich syngas production was studied. The food additives with Na + helped to the enhancement of H2 production. The Na2 CO3 showed the best catalytic performance on SCWG of unsorted food waste. The waste sorting was proved to be an effective way to optimize SCWG of food waste. Abstract: In China, waste sorting practice is not strictly followed, plastics, especially food packaging, are commonly mixed in food waste. Supercritical water gasification (SCWG) of unsorted food waste was conducted in this study, using model unsorted food waste by mixture of pure food waste and plastic. Different operating parameters including reaction temperature, residence time, and feedstock concentration were investigated. Moreover, the effect of three representative food additives namely NaCl, NaHCO3 and Na2 CO3 were tested in this work. Finally, comparative analysis about SCWG of unsorted food waste, pure food waste, and plastic was studied. It was found that higher reaction temperature, longer residence time and lower feedstock concentration were advantageous for SCWG of unsorted food waste. Within the range of operating parameters in this study, when the feedstock concentration was 5 wt%, the highest H2 yield (7.69 mol/kg), H2 selectivity (82.11%), total gas yield (17.05 mol/kg), and efficiencies of SCWG (cold gas efficiency, gasification efficiency, carbon gasification efficiency, and hydrogen gasification efficiency) were obtained at 480 °C for 75 min. Also, the addition of food additives with Na + promoted the SCWG of unsorted food waste. The Na2 CO3 showed the best catalytic performance on enhancement of H2 and syngas production. This research demonstrated the positive effect of waste sorting on the SCWG of food waste, and provided novel results and information that help to overcome the problems in the process of food waste treatment and accelerate the industrial application of SCWG technology in the future.